2003
DOI: 10.1002/jmri.10267
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated magnetic resonance hydrometry: An in vitro study

Abstract: Purpose:To demonstrate a quantitative approach to measuring fluid volumes with standard single shot RARE sequences. Materials and Methods:In phantom experiments, magnetic resonance hydrometry (MRH), in combination with various calibration phantoms (5 mL up to 500 mL) as internal standards, was used to quantify fluid volumes. In total, 16 volume phantoms were investigated with six different calibration phantoms. In addition, noise correction was implemented to correct the quantification results and to avoid the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…As previously shown in phantom experiments, smaller calibration volumes (<30 ml) would result in more error. Similarly, the position of the internal water control, close to the area of interest, is important to minimise coil and field inhomogeneity effects [14]. If this voxel does not contain 100% water, the calculated flow rate will be spuriously high.…”
Section: Discussionmentioning
confidence: 99%
“…As previously shown in phantom experiments, smaller calibration volumes (<30 ml) would result in more error. Similarly, the position of the internal water control, close to the area of interest, is important to minimise coil and field inhomogeneity effects [14]. If this voxel does not contain 100% water, the calculated flow rate will be spuriously high.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some researchers proposed a new method for quantification of pancreatic juice: secretin MR hydrometry (1,2). It was reported that the volume of pancreatic juice secretion significantly correlates with the maximal consistency of bicarbonate in the pancreatic juice after secretin stimulation (3,4); a decrease in the maximal consistency of bicarbonate was proposed as one of the early signs of a deficiency in the pancreatic exocrine function.…”
mentioning
confidence: 99%